Vitamin B12 status upon short-term intervention with a vegan diet: a randomized controlled trial in healthy participants - Lederer, Ann-Kathrin; Hannibal, Luciana; Hettich, Manuel; Behringer, Sidney; Spiekerkötter, Ute; Steinborn, Carmen; Gründemann, Carsten; Zimmermann-Klemd, Amy Marisa; Müller, Alexander; Simmet, Thomas; Schmiech, Michael; Maul-Pavicic, Andrea; et al. (Nutrients, 2019)
Vegans are at an increased risk for certain micronutrient deficiencies, foremost of vitamin B12. Little is known about the short-term effects of dietary change to plant-based nutrition on vitamin B12 metabolism. Systemic biomarkers of vitamin B12 status, namely, serum vitamin B12 and holotranscobalamin, may respond quickly to a reduced intake of vitamin B12. To test this hypothesis, 53 healthy omnivore subjects were randomized to a controlled unsupplemented vegan diet (VD, n = 26) or meat-rich diet (MD, n = 27) for 4 weeks. Vitamin B12 status was examined by measurement of serum vitamin B12, holotranscobalamin (holo-TC), methylmalonic acid (MMA) and total plasma homocysteine (tHcy). Holo-TC decreased significantly in the VD compared to the MD group after four weeks of intervention, whereas metabolites MMA and tHcy were unaffected. Body weight remained stable in both groups. VD intervention led to a significant reduction of cholesterol intake, and adequate profiles of nutrient and micronutrient status. Lower intake of vitamin B12 was observed in VD, which was mirrored by a lower concentration of serum vitamin B12 and reduced holo-TC after 4 weeks. Plasma holo-TC may be a fast-responding biomarker to monitor adequate supply of vitamin B12 in plant-based individuals.